2022
DOI: 10.1155/2022/4743041
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic and Antibacterial Effects of Chitosan Derivatives on Experimental Gastric Ulcers in Rats

Abstract: Gastric ulcer is an injury that develops on the lining of the stomach due to an imbalance between aggressive and defensive agents. Chitosan derivatives demonstrate promising biological activities in accelerating the healing activity of gastric lesions. Thus, this study aimed at investigating the healing activity of gastric lesion, induced by acetic acid (80%), of the chitosan derivative with acetylacetone (Cac) modified with ethylenediamine (Cacen) or diethylenetriamine (Cacdien). The biological activity was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Within our experimental design, IND was used as a positive control to study gastric damage produced by a COX-2 non-selective NSAID, while CTD was employed as a protective drug for IND-induced gastric damage against which to compare the gastroprotective effect of PBPs. The doses of the substances used in this experiment were taken from those reported in the literature to produce gastric ulcers with IND [61], to protect against gastric damage with CTD [62], and from previous studies in our laboratory in which PBPs showed good antioxidant and anti-inflammatory effects between doses 100 to 400 mg/kg [32].…”
Section: Antiulcerogenic Activity Of the Aqueous Extractmentioning
confidence: 99%
“…Within our experimental design, IND was used as a positive control to study gastric damage produced by a COX-2 non-selective NSAID, while CTD was employed as a protective drug for IND-induced gastric damage against which to compare the gastroprotective effect of PBPs. The doses of the substances used in this experiment were taken from those reported in the literature to produce gastric ulcers with IND [61], to protect against gastric damage with CTD [62], and from previous studies in our laboratory in which PBPs showed good antioxidant and anti-inflammatory effects between doses 100 to 400 mg/kg [32].…”
Section: Antiulcerogenic Activity Of the Aqueous Extractmentioning
confidence: 99%